070 Baseline characteristics and safety profile of patients with relapsing-remitting multiple sclerosis (RRMS) in the first interim analysis of the peginterferon BETA-1A treatment in the phase 4 plegridy observational program (POP). Issue 6 (24th May 2018) - Salvetti, Marco; Yun, Jang; Appiah-Badu, David; Sabatella, Guido; Naylor, Maria L
Abstract : Introduction: The 5 year, observational, phase 4 POP study explores the long-term safety and effectiveness of peginterferon beta-1a 125 mcg every 2 weeks in RRMS patients treated in real-world settings. This analysis presents interim data from POP on baseline characteristics, adverse events (AEs), and clinical effectiveness. Methods: POP is ongoing in >150 sites in 14 countries. Patients who initiated peginterferon beta-1a treatment either ≤31 days pre-enrolment (naive subgroup, 'PegNaive') or >31 days pre-enrolment (experienced subgroup, 'PegExperienced') will be followed for ≤5 years. Results: At the time of this analysis, 467 patients were included, 411 (88%) of whom were followed for ≥12 months. A total of 153 patients (33%) discontinued treatment, primarily due to AEs (55%) or lack of efficacy (13%). At baseline, mean age was 44.9 years, 76% of patients were female, and mean Expanded Disability Status Scale score was 1.9. Of the 371 patients (79%) with prior disease-modifying therapy use, 217 (58%) had been treated with intramuscular interferon beta-1a. More patients were PegNaive than PegExperienced (60% vs 40%). AEs were more common in PegNaive patients than in PegExperienced patients (35% vs 20%), as were AEs leading to treatment discontinuation (29% vs 15%). The most commonly reported AEs leading to treatment discontinuation in both groups were injection-site erythema and influenza-like illness. Serious AEs were reported in 5% of PegNaive and 9% of PegExperienced patients. A high proportion of patients in both groups were relapse free (PegNaive, 84.4%; PegExperienced, 81.5%). Conclusion: In this first interim analysis of the POP study, the safety profile was consistent with that observed in the phase 3 trial of peginterferon beta-1a. No new safety signals were observed. PegNaive patients were more likely than PegExperienced patients to experience AEs and discontinue treatment due to injection-site reactions and flu-like symptoms, highlighting a need for prophylactic mitigation strategies. Study support: Biogen